Diagnostic efficacy of Brucella abortus strain RB51 in experimentally inoculated Sprague-Dawley rats using western blot assay - Siddiqur Rahman; Byeong Kirl Baek (Journal of Infection in Developing Countries)
Background: To investigate the diagnosis and efficacy of Brucella abortus strain RB51 (SRB51) in experimentally inoculated Sprague-Dawley (SD) rat using western blot assay. Methodology: Female SD rats were orally administered with 1.0 x 107 colony forming unit (cfu) suspension of SRB51 and half of these SD rats were challenged at 4 weeks post inoculation with 1.0 x 109 cfu suspension of B. abortus biotype 1 isolated in South Korea. Sera of SD rats were monitored at regular intervals by western blot assay using whole cell antigen of B. abortus strain 1119-3 (S1119-3). The bacteriological examination of blood and clinical examination of the rats were also performed. Results: There were several bands at 120, 70, 45, 30, 20 kDa and clear specific bands were found after vaccination (20, 70 kDa) and challenge (15, 20, 45, 70, 120 kDa). The highest immune response was observed in sera 4 weeks post SRB51 vaccination. SRB51 was recovered from the blood of all of SRB51 inoculated rats until one week post vaccination and there were no clinical signs in that inoculated rats. Conclusions: It is concluded that the SRB51 elicits antigen specific immunity in SD rats based on western blot assay.